2019
DOI: 10.1088/1755-1315/343/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Green inventory controlling analysis of coal using the lot sizing technique: Lesson learned form nickel mining industry

Abstract: Companies, including PT Vale Indonesia (PTVI), generally should implement inventory control. PTVI use approximately 32,077 tons per month coal as a heating catalyst on the reducing furnace. There were several periods in 2017 and 2018 where the coal inventory exceed the safety stock and maximum stock level with the total cost of IDR 616,059,680.00 in 2017 and IDR 669,720,480.00 in 2018. In order to analyze and solve that stock problems, this research used the Lot-Sizing technique with Lot for Lot (LFL), Economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…backlogging, time windows, production capacity, inventory constraints, etc. Asmal et al (2019) compared and analyzed the Silver-Meal (SM) method and WW algorithm to minimize total inventory cost (TIC). The results revealed that about 35.08% of inventory cost was reduced by implementing the SM method and WW algorithm.…”
Section: Effect Of Lot-sizing Rules On Mrpmentioning
confidence: 99%
See 1 more Smart Citation
“…backlogging, time windows, production capacity, inventory constraints, etc. Asmal et al (2019) compared and analyzed the Silver-Meal (SM) method and WW algorithm to minimize total inventory cost (TIC). The results revealed that about 35.08% of inventory cost was reduced by implementing the SM method and WW algorithm.…”
Section: Effect Of Lot-sizing Rules On Mrpmentioning
confidence: 99%
“…backlogging, time windows, production capacity, inventory constraints, etc. Asmal et al. (2019) compared and analyzed the Silver–Meal (SM) method and WW algorithm to minimize total inventory cost (TIC).…”
Section: Literature Reviewmentioning
confidence: 99%